Healthy lifestyles in pre-service teachers in Israel: the impact of academic institutions - Ahdut-HaCohen, Ronit; Carmel, Paz (Frontiers in Public Health, 2023)
Purpose: This study examines the impact of academic institutions on changes to students' awareness and habits regarding a healthy lifestyle, specifically through nutrition and physical exercise, following the Covid-19 pandemic. Design and Subjects: In May 2020, quantitative online questionnaires were completed by 266 pre-service teachers (83.5% female), aged 19-63, who were studying at an academic institution in Israel. Setting: The questionnaire, which included health-related 15 items, as well as a number of demographic questions, was distributed via social media, academic mailing lists, and the researchers’ colleagues. Methods: The respondents were asked to provide socio-demographic data and information regarding their health-related habits, such as smoking and exercising, at two timepoints: prior to the Covid-19 pandemic and during the first lockdown in Israel (March-May 2020). Analysis: Statistical analysis included paired t-tests, Wilcoxon and McNemar tests, Pearsons’s correlations, and hierarchical regressions. Results: The academic institution’s promoting of a healthy lifestyle, as perceived by students, was found to contribute to the explained variance (EPV) of their maintaining a healthy lifestyle, prior to and during the Covid-19 pandemic (R2=9.4%, p<.001and R2=2.4%, p=.009, respectively), beyond the respondents’ demographic characteristics. Moreover, correlations were found between the institution's promoting of a healthy lifestyle at both timepoints. Respondents who perceived their institution as promoting a healthy lifestyle prior to the pandemic maintained healthier lifestyles than their peers; healthier lifestyles were also maintained by respondents who were unmarried, non-smokers, more educated, and watched less television. Finally, the institution’s promoting of a healthy lifestyle prior to the pandemic significantly contributed to the students’ maintaining a healthy lifestyle and healthy nutrition during the pandemic. Conclusions: The findings of this study highlight the impact of academic institutions on maintaining healthy lifestyles, even in times of crises and emergencies, thereby contributing to public health.